Who Produces Knowledge on Inclusive Education and Technology in Africa? A Bibliometric Mapping of Research Trends, Themes, and Collaboration - Aniku Ahmed Mohammed Moyini; Salih Mohamed Harun; Ali K Anami; Miiro Farooq; Stella Migide Madete (International Journal of Ethnoscience and Technology in Education, 2026)
This study examines who produces knowledge on inclusive education and technology in Africa and how that knowledge is organised in indexed scholarship. Records were exported from Scopus on 7 February 2026 and filtered to publications from 2021 to 2025, yielding a final corpus of 157 documents. A bibliometric design was applied to conduct performance analysis (publication trends, source productivity, and citation patterns) and science mapping (country collaboration networks, temporal overlays, and keyword-based conceptual structures). Results show rising publication output, but the wide dispersion of journals and loosely connected keyword clusters indicate parallel development rather than a consolidated conceptual core. Knowledge production is unevenly distributed, with South Africa leading affiliation occurrences, signalling selective visibility within indexed literature. Citation patterns are highly skewed, with a small set of anchor papers shaping debates on accessibility, digital inequality, and online learning. International collaboration is more established than intra-African collaboration, which appears thinner and less dense, and major collaborative ties remain largely stable between 2021–2023 and 2024–2025. Thematic evolution suggests movement from pandemic-era exclusion concerns toward post-crisis digital governance and emerging topics such as artificial intelligence and generative tools.